Integrated Culture of Fish with Micropropagated Plants in a Recirculatory System - Navya R (Department of Aquaculture, 2012)
Abstract- An experiment was designed to study an integrated recirculatory sytem with micropropagated aquarium plants, fish and indigenous filter materials like coir, vetiver and bamboo as the filter media. The plants selected for the study were Bacopa caroliniana, Anubias minima, Aponogeton ulvaceus, Rotala rotundifolia and Nymphoides cristata. The first part of the work was to standardise the micropropagation techniques for the above said plants. Murashige and Skoog medium (half and full strength) was used as the basal medium for the establishment of cultures. The explants varied from nodal segments, rhizome buds, leaf petioles and lateral buds. Surface sterilization was carried out with a range of sterilants like mercuric chloride solution, ethyl alcohol, sodium hypochlorite solution etc. for varying durations and concentrations depending on the type of explant. Effect of growth regulators on explants were studied using auxin IAA and cytokinins, BA and Kn. A liquid culture media with 1.5mg l-1 BA and 0.1mg l-1 Kn concentrations was the best medium for Bacopa caroliniana. A combination of auxin cytokinin like 1.5 mg l-1 BA and 1.0 mg l-1 IAA in liquid culture was the best medium for Rotala rotundifolia. In Nymphoides cristata, hormone concentration of 1.0 mg l-1 each of BA and IAA in liquid culture gave the best results. In Anubias minima, a full MS solid medium with 6.0 mg l-1 of BA gave better results compared to lower levels of BA. In vitro trials for Aponogeton ulvaceus was not successful due to the exudation of phenolic extracts in all the treatments which eventually lead to the death of the tissues. Hardening success was 90 percent, 100 percent, 70 percent, 100 percent in the case of Anubias minima, Nymphoides cristata, Rotala rotundifolia and Bacopa caroliniana respectively. The micropropagated plants were incorporated in the recirculatory system along with fish and three different biofilter materials like coir, vetiver and bamboo splits. The study focused mainly on the filtering efficiency of the three filters based on the nitrification curves. The plants were included in the system to be a part of biofilter and their exclusive role in nitrification was not studied since this is a preliminary work. A nitification graph was plotted with the observed values of ammonia, nitrite and nitrate in the three different biofilter systems and compared with a control. It was inferred that coir fibres were the best of filter materials tried in nitrification followed by bamboo and vetiver. The control system took more time (45 days) in stabilizing ammonia levels due to lack of a substratum for growing nitrifying bacteria.